Whither multilateral development finance? - Robert Wihtol (Asian Development Bank Institute (ADBI), 2014)
Multilateral development finance is at a critical juncture. In the past 70 years, it has developed through four distinct stages. The Bretton Woods conference established the World Bank and the International Monetary Fund in 1944 to finance post-war reconstruction and stabilize the global economy. The second stage saw the establishment of regional development banks in the 1950s and 1960s. This was followed by the emergence of subregional banks. In the fourth stage, from the mid-1970s to the 2000s, specialized vertical funds were established to address global issues, and private development finance expanded. The multilateral financial architecture now has a multitude of development banks and funds. As the architecture enters the next stage, the development agenda is changing rapidly. Financially constrained traditional donors are unwilling to recapitalize the existing banks, while emerging donors want to reduce the role of traditional donors and increase their own funding. Emerging-economy bilateral programs are expanding. At the same time, new multilateral initiatives are advancing fast. The BRICS countries' New Development Bank and related contingent reserve and the PRC's Asian Infrastructure Investment Bank initiative have added to the pressure for reform, and to the risk of fragmentation. An alternative financial architecture may take shape led by emerging economies, playing down coordination and well-established development, safeguard, and governance criteria. However, there is also an opportunity for genuine reform to ensure a new and innovative multilateral architecture.
Keywords: F33; F34; F35; O19; 330